Performance Evaluation Of The Trans Metro Deli Program In Improving Public Transportation Services In Medan City - Hasrul, Savira; Sihombing, Tunggul (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2024)
This study aims to determine and describe the Performance Evaluation of the Trans Metro Deli Program in Improving Public Transportation Services in Medan City. At the beginning of its operation, Trans Metro Deli received good views from the public because it could be enjoyed for free. However, the implementation of the Trans Metro Deli program, which has been almost 3 years, has not fully addressed the problems in the field, so it is necessary to evaluate the performance of the Trans Metro Deli program. The purpose of this study was to identify and describe in detail performance evaluation of the Trans Metro Deli Program by looking at Helmut Wollman's evaluation indicators: Effectiveness, Efficiency and Equity. This research use descriptive qualitative approach. Based on the research results, performance evaluation of the Trans Metro Deli program was carried out using three evaluation indicators: First, effectiveness is running well but is hampered by the problem of illegal parking which has not been resolved. Second, efficiency needs to be considered to increase the number of human resources in the technology department. Third, Equity is not yet optimal, this can be seen from the 217 bus stops, only 60 of them were made permanent while the rest were damaged. Therefore, it is very necessary to improve the transportation facilities and infrastructure in Medan that are able to meet the needs of all levels of society, especially for the disabled and the elderly.